2008
DOI: 10.2174/1875039700801010099
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Human Salivary Peptidome by Differential Peptide Display and LC-MS/MS Overview Sequencing

Abstract: Abstract:In recent years interest in the characterization of the human salivary proteome has increased in order to explore its diagnostic potential. Major constituents of human saliva are highly polymorphic proteins that may have biological roles in oral lubrication and protection, e.g. proline-rich proteins (PRPs), statherins, histatins and cystatins. Interestingly, many of theses proteins are rapidly degraded in the oral cavity by host-and bacteria-or viral-derived proteases. Thus, comprehensive analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…In spite of the high intra and inter‐individual qualitative and quantitative diversity of the salivary peptidome (Le Yondre et al , ; Quintana et al , ; Vitorino et al , ), the inter‐individual comparison between all studied subjects showed an overall higher amount of protein fragments in diabetic samples. Peptidomic data (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In spite of the high intra and inter‐individual qualitative and quantitative diversity of the salivary peptidome (Le Yondre et al , ; Quintana et al , ; Vitorino et al , ), the inter‐individual comparison between all studied subjects showed an overall higher amount of protein fragments in diabetic samples. Peptidomic data (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…After 18 h and 115 h of incubation, the majority of the eluted peptides belonged almost exclusively to the different PRP isoforms, suggesting that these proteins display the highest susceptibility to ex vivo proteolysis. Cleavage site analysis showed that the peptide bond between GlnGly residues was the preferential site for proteolysis, which is in agreement with previous findings [29][30][31][32]. Interestingly, the formation of the new PRPs peptides is associated with a time-dependent profile of proteases, a variation never reported so far, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Despite inter-individual variability, PRPs, P-B peptide, histatin 1 and 3, mucin 7, polymeric immunoglobulin receptor and statherin represented the most susceptible salivary proteins to proteolysis in vivo, as proven by the number of peptides identified to these proteins at T0 (Table 1) which is corroborated by the LC-MS/MSbased characterization of whole salivary peptidome [29][30][31]. Protein fragments at T0 were attributed to the activity of CTSL1 and MEP1A.…”
Section: Discussionmentioning
confidence: 66%
“…Amado et al (6) evaluated the salivary peptidome of 10 patients with head and neck cancer (HNC) and identified 1834 fragments belonging to 289 unique proteins. Despite the high intra-and interindividual qualitative and quantitative diversity of the salivary peptidome among subjects (35,65,66), diabetics showed an overall higher amount of protein fragments supported by higher activity in zymography analysis. Recently, our research group focused on the evaluation of the effect of more than 12 years of type 1 diabetes mellitus (T1DM) and related complications on the salivary peptidome.…”
Section: The Missing Link: Connecting Peptides To Peptidasesmentioning
confidence: 89%